In vitro and in vivo antiplasmodial activities of leaf extracts from Sonchus arvensis L. - Dwi Kusuma Wahyuni; Sumrit Wacharasindhu; Wichanee Bankeeree; Sri Puji Astuti Wahyuningsih; Wiwied Ekasari; Hery Purnobasuki; Hunsa Punnapayak; Sehanat Prasongsuk (BMC, 2023)
Abstract Background Malaria continues to be a global problem due to the limited efficacy of current drugs and the natural products are a potential source for discovering new antimalarial agents. Therefore, the aims of this study were to investigate phytochemical properties, cytotoxic effect, antioxidant, and antiplasmodial activities of Sonchus arvensis L. leaf extracts both in vitro and in vivo. Methods The extracts from S. arvensis L. leaf were prepared by successive maceration with n-hexane, ethyl acetate, and ethanol, and then subjected to quantitative phytochemical analysis using standard methods. The antimalarial activities of crude extracts were tested in vitro against Plasmodium falciparum 3D7 strain while the Peter's 4-day suppressive test model with P. berghei-infected mice was used to evaluate the in vivo antiplasmodial, hepatoprotective, nephroprotective, and immunomodulatory activities. The cytotoxic tests were also carried out using human hepatic cell lines in [3(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide] (MTT) assay. Result The n-hexane, ethyl acetate, and ethanolic extracts of S. arvensis L. leaf exhibited good in vitro antiplasmodial activity with IC50 values 5.119 ± 3.27, 2.916 ± 2.34, and 8.026 ± 1.23 μg/mL, respectively. Each of the extracts also exhibited high antioxidant with low cytotoxic effects. Furthermore, the ethyl acetate extract showed in vivo antiplasmodial activity with ED50 = 46.31 ± 9.36 mg/kg body weight, as well as hepatoprotective, nephroprotective, and immunomodulatory activities in mice infected with P. berghei. Conclusion This study highlights the antiplasmodial activities of S. arvensis L. leaf ethyl acetate extract against P. falciparum and P. berghei as well as the antioxidant, nephroprotective, hepatoprotective, and immunomodulatory activities with low toxicity. These results indicate the potential of Sonchus arvensis L. to be developed into a new antimalarial drug candidate. However, the compounds and transmission-blocking strategies for malaria control of S. arvensis L. extracts are essential for further study.